Decisional Procrastination in Academic Settings: The Role of Metacognitions and Learning Strategies - de Palo, Valeria; Monacis, Lucia; Miceli, Silvana; Sinatra, Maria; Di Nuovo, Santo (Frontiers in Psychology, 2017)
Nowadays, university students suffer from a broad range of problems, such as educational underachievement or the inability to control themselves, that lead to procrastination as a consequence. The present research aimed at analyzing the determinants of decisional procrastination among undergraduate students and at assessing a path model in which self-regulated learning strategies mediated the relationship between metacognitive beliefs about procrastination and decisional procrastination. 273 students from Southern Italy filled out a questionnaire composed by: the socio-demographic section, the Metacognitive Beliefs About Procrastination Questionnaire, the procrastination subscale of the Melbourne Decision Making Questionnaire, and the Anxiety, the Time Management, and the Information Processing subscales of the Learning and Study Strategies Inventory. Results showed that the relationship between negative and positive metacognitive beliefs about procrastination and decisional procrastination was mediated only by time management and anxiety. Such findings underlined the crucial role played by learning strategies in predicting the tendency to delay decisional situations and in mediating the relationship between metacognitive beliefs about procrastination and decisional procrastination.